2008
DOI: 10.1007/s12185-008-0132-1
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of 728 cases of non-Hodgkin lymphoma from a single laboratory in Shanghai, China

Abstract: The frequency of subtypes of lymphoid neoplasms was determined in a prospective series of 831 patients presenting at 29 Shanghai hospitals over a 4-year period. Diagnosis and classification was established in a single laboratory according to the 2001 WHO classification system. The frequency of non-Hodgkin lymphoma was 87.6% (n = 728) and Hodgkin lymphoma was 12.4% (n = 103). The most prevalent NHL subtypes diagnosed using WHO criteria were diffuse large B cell lymphoma (DLBCL), precursor B lymphoblastic leukem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
31
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 22 publications
(28 reference statements)
10
31
3
Order By: Relevance
“…Our findings are in agreement with previous results, showing the relatively higher proportions of patients with overall NHL and T/NK-cell neoplasms, and the relatively lower proportions of patients with FL, CLL/SLL, and HL among Korean individuals compared with those of Western populations (Supplementary Table III) [4][5][6][7][8][9][10][11][12][13][14][15][16][17]19,21,23,37].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Our findings are in agreement with previous results, showing the relatively higher proportions of patients with overall NHL and T/NK-cell neoplasms, and the relatively lower proportions of patients with FL, CLL/SLL, and HL among Korean individuals compared with those of Western populations (Supplementary Table III) [4][5][6][7][8][9][10][11][12][13][14][15][16][17]19,21,23,37].…”
Section: Discussionsupporting
confidence: 92%
“…As for MALT lymphoma, the frequency observed in this study was similar to that of previous Korean data, and higher than the Japanese or USA data (Supplementary Table III) [4][5][6][7][8][9][10][11][12][13][14][15][16][17]19,21,23,37]. In agreement with previous findings, we found that the proportions of Korean patients with CLL/SLL and FL were low; this is in contrast to the increased rate of FL in Japan, where this subtype now accounts for 20% of all NHLs [12,22,27,45].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The incidence and distribution of T-and NK-cell lymphomas in several Asian countries is summarized in Fig. 1 and Table 1 [ [4][5][6][7][8][9][10][11][12][13][14][15].The frequencies of T-and NK-cell lymphomas seem to increase from West to East Asia. The occurrence rate of Tand NK-cell lymphomas are relatively low (\20 % of NHL) mainly in West Asia (Turkey 16.2 %, Iraq 19 %, and Kuwait 18 %) and South Asia (Pakistan 11.3 %, and India 20.2 %), but relatively high mainly in East Asia (China 32.5 %, Korea 22 %, and Japan 24.9 %) and Southeast Asia (Thailand 25 %).…”
mentioning
confidence: 99%